Implementation of Traffic Accident Insurance for Violations of Traffic Regulations in the National Social Security System - Cahyoko, Ranto; Hafidz, Jawade (Jurnal Daulat Hukum, 2024)
Analysis of the process of implementing traffic accident insurance by PT Jasa Raharja for violations of traffic regulations. The existence of PT Jasa Raharja is really needed by the public to get road traffic accident insurance protection. This research aims to study and analyze the implementation of traffic accident insurance for violations of traffic regulations. As well as reviewing and analyzing obstacles in implementing traffic accident insurance for violators of traffic regulations. The approach method used in this research is sociological juridical. The specifications of this research are analytical descriptive. The data sources used are primary data and secondary data. Traffic violations committed by the public will cause traffic accidents, because in principle traffic accidents must begin with a traffic violation. The implementation of providing compensation to drivers who do not have a driving license or who commit traffic violations has currently been provided with ex-gratia compensation for two or more vehicles. The provision of ex gratia compensation for two or more vehicles is based on the policy of the head of the representative which aims to provide guaranteed accident protection for the public as road users. PT Jasa Raharja Board of Directors Decision Number KEP/132/2023. The essence of this policy is to limit ex-gratia payments more selectively. The Board of Directors' decision Number KEP/132/2023 is contrary to Article 14 of Government Regulation Number 18 of 1965. Article 14 of Government Regulation Number 18 of 1965 requires changes to the government regulation.